2022
DOI: 10.1021/acsaem.2c03322
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Benzodithiophene-Based Donor–Acceptor-Type Covalent Triazine Frameworks with Tunable Structure for Photocatalytic Hydrogen Evolution

Abstract: The introduction of donor–acceptor (D–A) motifs into organic semiconductors has been considered as one of the effective strategies to regulate photocatalytic activity. Herein, D–A-type benzodithiophene-based covalent triazine framework materials (BDT-CTFs) have been reported. It has been shown that the valence band and conduction band positions, band gaps, and electron–hole separation efficiency can be adjusted by altering the D/A ratio in the BDT-CTF photocatalytic materials. It has been revealed that the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…A series of BDT-based CTFs were synthesized to investigate the structure-activity relationship in these materials with different D-A ratios. 93 The experimental results showed that an appropriate D-A ratio in BDT-based CTFs led to efficient charge separation and low electron-hole recombination rates, which greatly promoted the photocatalytic activity for the HER.…”
Section: Donor-acceptor (D-a)mentioning
confidence: 96%
See 3 more Smart Citations
“…A series of BDT-based CTFs were synthesized to investigate the structure-activity relationship in these materials with different D-A ratios. 93 The experimental results showed that an appropriate D-A ratio in BDT-based CTFs led to efficient charge separation and low electron-hole recombination rates, which greatly promoted the photocatalytic activity for the HER.…”
Section: Donor-acceptor (D-a)mentioning
confidence: 96%
“…Notably, in these D-A CTF materials, the role of triazine can vary, acting as either an electron donor or acceptor within the CTF structure, owing to the various electronic properties between triazine and the aforementioned moieties. 85,87,[91][92][93] Thiophene or benzothiadiazole (BT) units have been introduced as dopants to enhance the charge carrier separation and migration in CTF-based photocatalysts. Experimental results and density functional theory (DFT) calculations have demonstrated that CTFs modied with Th or BT exhibit extended absorption of visible light and more efficient charge carrier transfer compared to pristine CTF-1.…”
Section: Donor-acceptor (D-a)mentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18][19] And with triazine moieties as inherent acceptors, the construction of donor-acceptor configuration in CTFs has been regarded as one of the most convenient and effective methods to achieve this goal. [20][21][22][23][24][25] However, most of the published studies have focused on qualitatively investigating the effects of various donor groups on the catalytic properties of CTFs, while few reports have quantitatively investigated the effects of donor unit content (Dcontent) on the optical properties and photocatalytic activities of CTFs.…”
Section: Introductionmentioning
confidence: 99%